Gambaran Pelaksanaan Program Sanitasi Total Berbasis Masyarakat di Desa Oelpuah Kecamatan Kupang Tengah - Megy Justin Ballbessy; Soni Doke; Ribka Limbu (Media Kesehatan Masyarakat, 2020)
Community-Based Total Sanitation (STBM) is an approach and paradigm for sanitation development in Indonesia that emphasizes the principle of non-subsidies through community empowerment in order to build hygienic and sanitary behavior. Indonesia generally has low coverage of basic sanitation facilities. One of the areas in East Nusa Tenggara Province that has become a priority for STBM Program implementation is Oelpuah Village, Central Kupang District, located in Kupang Regency. The problem in Oelpuah Village is the lack of knowledge in the community related to hygiene and sanitation. The purpose of this research was to get an overview of the implementation of the five pillars of STBM in Oelpuah Village, Central Kupang District in 2020. This research was descriptive. The research was carried out in five hamlets in Oelpuah Village. The sample was selected by random method. The population in this study were all 354 family heads in Oelpuah Village and the sample in this study were 188 heads of households. The results showed that Pillar I, IV, and V were categorized as not implemented Pillar II and IIIwere included in the criteria for implementation.